The use of the amplification refractory mutation system (arms) in the detection of rare beta-thalassemia mutations in the Malays and Chinese in Malaysia - Chan, Yoke Fun; Tan, Kim Lim; Wong, Yean Ching; Wee, Yong Chui; Yap, Sook Fan; Tan, Mary Anne Jin Ai (SEAMEO Regional Tropical Medicine and Public Health Network, 2001)
Molecular characterization and prenatal diagnosis for beta-thalassemia can be carried out using the Amplification Refractory Mutation System (ARMS). The ARMS is a rapid and direct molecular technique in which beta-thalassemia mutations are visualized immediately after DNA amplification by gel electrophoresis. In the University of Malaya Medical Center, molecular characterization and prenatal diagnosis for beta-thalassemia is carried out using ARMS for about 96 of the Chinese and 84.6 of the Malay patients. The remaining 4 and 15.4 of the uncharacterized mutations in the Chinese and Malay patients respectively are detected using DNA sequencing. DNA sequencing is an accurate technique but it is more time-consuming and expensive compared with the ARMS. The ARMS for the rare Chinese beta-mutations at position -29 (A-->G) and the ATG-->AGG base substitution at the initiator codon for translation in the beta-gene was developed. In the Malays, ARMS was optimized for the beta-mutations at codon 8/9 (+G), Cap (+1) (A-->C) and the AATAAA-->AATAGA base substitution in the polyadenylation region of the beta-gene. The ARMS protocols were developed by optimization of the parameters for DNA amplification to ensure sensitivity, specificity and reproducibility. ARMS primers (sequences and concentration), magnesium chloride concentration, Taq DNA polymerase and PCR cycling parameters were optimized for the specific amplification of each rare beta-thalassemia mutation. The newly-developed ARMS for the 5 rare beta-thalassemia mutations in the Chinese and Malays in Malaysia will allow for more rapid and cost-effective molecular characterization and prenatal diagnosis for beta-thalassemia in Malaysia.